United we adapt: communities of practice to face the CoronaVirus crisis in higher education. Issue 4 (2nd October 2021) - Bolisani, Ettore; Fedeli, Monica; Bierema, Laura; De Marchi, Valentina
ABSTRACT: The paper contributes to the knowledge management literature by arguing how a community of practice (CoP) can react to a situation of crisis quickly, providing support to the whole organisation where it operates. This work examines a CoP of "change agents" at the University of Padova, how it coped with the emergency and the risk of disruption caused by COVID-19, and how it supported the transformation of teaching and learning in higher education. Especially, the purpose of this research is to understand the impact of a crisis on a CoP and on its functioning. Through an in-depth case study, the paper presents evidence of the evolution of the community, and the concrete support offered to faculty coping with the emergency. The crisis provided the impetus to strengthen the relationships among members, improve the sense of belonging, and empower the entire community.